ChemInform Abstract: Synthesis and Late‐Stage Functionalization of Complex Molecules Through C—H Fluorination and Nucleophilic Aromatic Substitution. Issue 7 (29th January 2015) - Fier, Patrick S.; Hartwig, John F.
Abstract The selectivity of the first step, the fluorination, is examined on medicinally relevant heteroaromatic substrates with several electronically deferring mono or 3, 5‐disubstituted pyridines (such as (XIV)).